2010
DOI: 10.1111/j.1365-3024.2009.01182.x
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of intestinal barrier and secretory function as well as egg excretion during intestinal schistosomiasis occur independently of mouse mast cell protease-1

Abstract: Deposition of Schistosoma mansoni eggs in the intestinal mucosa is associated with recruitment of mucosal mast cells (MMC) expressing mouse mast cell protease-1 (mMCP-1). We investigated the involvement of mMCP-1 in intestinal barrier disruption and egg excretion by examining BALB/c mice lacking mMCP-1 (Mcpt-1(-/-)). Tissue and faecal egg counts from 6 weeks until 12 weeks post-infection (w p.i.) revealed no differences between wild type (WT) and Mcpt-1(-/-)mice. Using chamber experiments on ileal tissue revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…In mammals, compound 48/80 is a potent degranulation agent of connective tissue‐type MCs with no effect on mucosal MCs (Enerbäck, '66; Enerbäck and Lundin, '74; Koibuchi et al, '85; Ikawati et al, 2000), though recently Rychter et al (2010a, b) challenged such view and reported evidence that calcitonin gene‐related peptide receptor activation induced piecemeal release of protease‐1 from mouse bone marrow‐derived mucosal MCs in vitro. In fish, compound 48/80 exerts a less potent degranulating effect on MCs without a clear tissue differentiation (Vallejo and Ellis, '89; Reite, '97; Schmale et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, compound 48/80 is a potent degranulation agent of connective tissue‐type MCs with no effect on mucosal MCs (Enerbäck, '66; Enerbäck and Lundin, '74; Koibuchi et al, '85; Ikawati et al, 2000), though recently Rychter et al (2010a, b) challenged such view and reported evidence that calcitonin gene‐related peptide receptor activation induced piecemeal release of protease‐1 from mouse bone marrow‐derived mucosal MCs in vitro. In fish, compound 48/80 exerts a less potent degranulating effect on MCs without a clear tissue differentiation (Vallejo and Ellis, '89; Reite, '97; Schmale et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Degranulation of MCs occurred as response to parasite, bacteria, and degranulating agent in natural or experimental conditions (Vallejo and Ellis, '89; Flaño et al, '96; Reite, '97; Matsuyama and Iida, '99; Schmale et al, 2004; Dezfuli and Giari, 2008; Rychter et al, 2010a, b). Little work has been carried out to detect experimentally the effect of MCs degranulation on smooth muscle cell contraction in fish; nonetheless, branchial vasomotor effect has been reported in Reite ('97) and in Mulero et al (2007).…”
mentioning
confidence: 99%
“…A role for mouse MCP1 in the increased permeability observed 8 weeks after infection with the trematode S. mansoni was ruled out using mMCP1 ¡/¡ mice. 65 Given that the 2 most consistent findings observed in humans having irritable bowel syndrome (IBS) are increased gut permeability and mastocytosis, 66 one wonders if helminth therapy aimed at treating autoinflammatory disease 34 might predispose an individual to IBS-like symptoms.…”
Section: Increased Epithelial Permeability Triggered By Infection Witmentioning
confidence: 99%
“…Bone marrow‐derived mast cells (BMMC) abundantly contain the granule chymases mMCP‐1 and mMCP‐2, 27 which are uniquely present in the MMC population and are not expressed in CTMC 28,29 . The major constituent of mouse MMC granules mMCP‐1 can modulate the barrier and transport properties of the intestinal epithelium 30,31 . Moreover, the BMMC express the integrin α E β 7 32 which is typical of cells predominantly located in the mucosal epithelium 32,33 .…”
Section: Introductionmentioning
confidence: 99%